“ANALISIS IMPLEMENTASI KEBIJAKAN E-FAKTUR DALAM UPAYA PENINGKATAN PENERIMAAN NEGARA PADA KPP PRATAMA TEBET TAHUN 2016” - Idar Rachmatulloh; Putri Y Pamungkas (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
In 2013 - 2014 value an invoice tax fictitious up by Rp.150.600.000.000,00, for that Direktorat Jenderal Pajak is trying to create E-Faktur for the purpose of removing the number of an invoice tax fictitious would encourage state revenues. This research in its implementation use the theory Edward III. In this research researchers want to know the implementation of E-Faktur that had taken from the beginning experiments on Java and Bali in 2015 and are valid nationwide in July 2016 .In this research researchers used research methodology qualitative is data analysis the discussion descriptive comparing between the realization of with the potential E-Faktur related state revenues. The research, in 2015 when E-Faktur applied the first phase in Java and Bali increase from 2014 where E-Faktur has not been applied yet. And on 2016 when E-Faktur set of the national scale, state revenues increase to 12,40 % .This explains that E-Faktur can help to improve state income.